KNOWLEDGE REGARDING PREVENTION OF VENTILATOR ASSOCIATED PNEUMONIA AMONG NURSES IN A TERTIARY HOSPITAL, RUPANDEHI, NEPAL - Ghimire, Sulochana; Neupane, Srijana (Journal of Universal College of Medical Sciences, 2018)
Introduction: Ventilator-associated pneumonia (VAP) is the most frequent and severe infection acquired in the intensive care unit, leading to prolonged mechanical ventilation and excess mortality. This study has been conducted to find out the knowledge regarding prevention of Ventilator Associated Pneumonia (VAP) among nurses.Materials and Methods: A descriptive cross-sectional study was conducted to find out the knowledge regarding prevention of VAP among nurses. Fifty one respondents working in different intensive care areas (ICU, CCU, NICU and PICU) of Universal College of Medical Sciences - Teaching Hospital were selected as the study sample by using census method.  Self-administered structured questionnaire was used to collect the data and collected data were analyzed by using descriptive and inferential statistics with SPSS software version 16.Results: The findings of the study revealed that 41.2% and 86.2% of the respondents had knowledge regarding meaning and causative agent of VAP respectively. The mean percentage of risk factors of VAP and VAP bundle were 86.2 and 61.3 respectively. About 37% of the respondents had knowledge regarding oral care with chlorhexidine, 86.3% had knowledge that ventilator circuit should be changed for every new patient and 39.2% of the respondents had knowledge that closed suction system prevents VAP. The findings of the study revealed that 49.1% of the respondents had high knowledge and 7.8% had average knowledge. There was no statistically significant association between respondents' level of knowledge regarding prevention of VAP with respondents' working experience (p=O.493) and qualification (p=O.459).Conclusion: Based on the study findings, it is concluded that almost half of the respondents have high knowledge regarding prevention of VAP. Besides this, respondents have high knowledge regarding VAP (meaning, causative agent, risk factors, principles and complications) and VAP prevention by positioning, airway humidification and suctioning and low knowledge is found on component of VAP bundle, oral care to reduce   VAP and ideal cuff pressure of endotracheal tube.Journal of Universal College of Medical SciencesVol. 6, No. 1, 2018, Page: 27-31